Molten Salt Synthesized Submicron Perovskite La1–xSrxCoO3 Particles as Efficient Electrocatalyst for Water Electrolysis - Mohan, Swati; Mao, Yuanbing (Frontiers in Materials, 2020)
Perovskite oxides are an important and effective class of mixed oxides which play significant role in the fields of energy storage and conversion systems. Here we present a series of cobaltite perovskite LaCoO3 particles which have been doped with 0, 5, 10, 20 and 30% of Sr2+ and have been synthesized by a combined sol-gel and molten-salt synthesis procedure, which provides regular morphology of the particles. These Sr2+ doped LaCoO3 particles have been characterized by powder X-ray diffraction, Raman spectroscopy, infrared spectroscopy, X-ray photoelectron spectroscopy, and scanning electron microscopy. Moreover, these Sr2+ doped LaCoO3 particles have been demonstrated as efficient catalyst for oxygen evolution reaction (OER) based on the measured specific capacitance, total charge, most accessible charge, electrochemically active surface area, and roughness factor using rotating disk and rotating ring-disk electrode techniques. The 30% Sr2+ doped LaCoO3 sample shows enhanced electrocatalytic OER activity in 0.5 M H2SO4 media compared to the LaCoO3 samples doped with 0, 5, 10, 20% Sr2+. Among all five LaCoO3 samples, the doped LaCoO3 samples demonstrate better OER activity than the undoped sample.